Scientific preservation and usage of library materials in National Archives, Nepal National Library and Tribhuvan University Central Library - VAIDYA, BINA (TULSSAA Journal, 2025)
This article shows importance and utility of microforms for preservation of rare printed materials for future use. It also narrates the history of preservation in the world along with a glimpse of Nepal. It describes the steps and technologies used for producing the microforms and offer various measures for safe handling and durable storage systems. And finally it gives the names of libraries in Nepal where the micrographic equipments have been installed and processing works are being carried out.TULSSAA Vol.4(3) 2006 pp.14-18